Between good and evil: linguistic explication of the ambivalence of the universe in O. Dovhiy's poetry - Strokal , Oleksandr (Current issues of Ukrainian linguistics: theory and practice, 2020)
The peculiarities of the linguistic expression of contrast reception in Oleksii Dovhiy's poetry are analyzed in the article. The author deals with such theoretical issues as а poetic text and the reception of contrast in poetry. Аnalyzing the role of evaluation in а poetic text, the author emphasizes the importance of its functions in verse language and human consciousness as a means of structuring cognizable reality. In the process of researching these problems, the author finds that in O. Dovhiy's poetic language, there are units that name both positive and negative realities within the same context, reflecting the artist's view of a particular organization of the world and the universe. Analyzing language units used by the poet to denote the phenomena of nature, elements of landscape and their attributes, we have noticed that in some cases such language units are used by the artist to reflect life challenges that influence the  existential choice  of a lyrical hero. Depicting the inner world of a lyrical hero, Oleksii Dovhiy uses a number of linguistic constructions that help the artist to emphasize the importance and the decisive role in such a choice of the inner willpower effort-decision of his hero. The analysis made it possible to distinguish among others a number of linguistic units that, when used in one or another context, create the same images with different axiological semantics. Such peculiarities of contextual use of the respective lexemes made it possible to form a separate group of nominations of contrasting images. The researcher has found out that one of Oleksii Dovhiy's brightest ambivalent images is the image of a word. In one case, this image is understood by the lyric hero as a word that has no weight and a weighty word. In the other case we have an emphasis on such a characteristic as the power of a word, its healing properties. Alongside the image of a word, a series of verbalizers is presented in the artist's poetry to denote the image of fire as a creative and at the same time destructive beginning. Stylistic analysis of the features of contextual functioning of lexemes for the designation of environmental phenomena has revealed a number of language units with stereotypically negative semantics, which in the literary context acquire a neutral or a positively marked tonality. It is proved that in Oleksii Dovhiy's poetry the aforementioned linguostylistic feature is unique
Keywords: contrast, good and evil, linguistic worldview, Oleksii Dovhiy's poetry.